Epidemiologic factors for TMJ disorders: Gender, age, and general joint mobility - IGARASHI, Kazuyoshi; HIYAMA, Shigetoshi; KATO, Yoshiyuki; KURODA, Takayuki (Journal of the Japanese Society for the Temporomandibular Joint, 1998)
The purpose of this study was to investigate the relationship between the etiologic factors such as gender, age, and general joint mobility and TMJ disorders. Subjects comprised of 110 randomly selected orthodontic patients (78 females and 32 males) aged 9-37 years with a mean of 22.1 years. Joint mobility was assessed and graded by means of the hypermobility score of Beighton et al. Fifty of 78 females and 17 of 32 males showed the symptoms of TMJ disorders (symptomatic patients). TMJ sound was observed in every symptomatic patient. Relative risks- the incidence among the subjects in a particular category of exposure divided by the corresponding rate in the comparison category- for TMJ disorders associated with specific factors were adjusted for potentially compounding factors by logistic-regression analysis. No significant gender difference was observed in the prevalence of TMJ disorders. However, TMJ and muscular pain and difficulty in mouth opening were more frequently observed in female symptomatic patients than male patients. There was a significant relative risk of TMJ disorders associated with increasing age (relative risk, 1.28; P<0.001). Higher score of general joint mobility was also significantly associated with an increased risk of TMJ disorders (relative risk, 1.40; P=0.02).